Metformin use and mortality and length of stay among hospitalized patients with type 2 diabetes and COVID-19: A multiracial, multiethnic, urban observational study - Miao, Emily; Zhang, Kaleena; Liu, Jianyou; Lin, Juan; Yoo, Donna; George, Claudene J. (Frontiers in Endocrinology, 2022)
Introduction: Diabetes mellitus is a common comorbidity among patients with coronavirus disease 2019 (COVID-19). Diabetic patients with COVID-19 have a two-fold increased risk of death and tend to have more severe infection compared to the general population. Metformin, a first-line medication for diabetes management, has anti-inflammatory and immunomodulatory effects. Previous studies focusing on metformin and COVID-19 clinical outcomes have had mixed results, with some showing a mortality benefit or decreased complications with metformin use. To date, few studies have analyzed such outcomes among a diverse, multiracial community. Methods: This was a retrospective review of patients with Type 2 diabetes and a confirmed COVID-19 infection admitted to an urban academic medical center from January 1, 2020 to May 7, 2020. Baseline characteristics were collected. The primary outcomes of the study were in-hospital mortality and length of stay (LOS). Results: A total of 4462 patients with Type 2 diabetes and confirmed COVID-19 were identified. 41.3% were Black, and 41.5% were Hispanic. There were 1021 patients in the metformin group and 3441 in the non-metformin group. Of note, more participants in the metformin group had comorbid disease and/or advanced diabetes. We found no statistically significant differences between the metformin and non-metformin group in in-hospital mortality (28.1% vs 25.3%, P=0.08) or length of hospital stay in days (7.3 vs. 7.5, P=0.59), even after matching patients on various factors (29.3% vs. 29.6%, P=0.87; 7.7 vs. 8.1, P=0.23). Conclusion: While patients had more comorbid disease and advanced diabetes in the metformin group, there were no significant differences with regard to in-hospital mortality or length of stay due to COVID-19 compared to the non-metformin group. Prospective studies are needed to determine if there is clinical benefit for initiating, continuing, or re-initiating metformin in patients hospitalized with COVID-19.